The synergistic effects of customer orientation and knowledge management on firm performance - Zhang, Xinghui; Alwie, Aryaty Binti; Rosli, Anita Binti (Arts and Science Press, 2024)
This review paper explores the intricate relationship between Customer Orientation, Knowledge Management, andFirm Performance, providing a comprehensive analysis of their collective impact on contemporary business practices. Anchored in a robust conceptual framework, the literature review traces the historical evolution of both CustomerOrientation and Knowledge Management, elucidating their theoretical foundations and setting the stage for the analysis. The paper examines the drivers and dimensions of Customer Orientation, identifying factors influencing its adoptionand strategies for measurement within organizations. Simultaneously, it delves into Knowledge Management, exploringdiverse models and best practices for implementation. By analyzing the interplay between Customer OrientationandKnowledge Management, the study uncovers synergies, explores successful integration through real-world case studies, and addresses the challenges and limitations of this dynamic relationship. The paper employs a meticulous methodology, outlining research design, data collection, and analysis with clear criteria for selecting and reviewing relevant studies. Empirical evidence is presented, including quantitative findings, qualitative insights, and a synthesis of results, todetermine the tangible impact on Firm Performance. The implications for business practices are discussed, offeringpractical applications, managerial recommendations, and insights into future trends. The paper concludes withasummary of key findings, highlighting contributions to the field and calling for further research. This reviewserves asavaluable resource for academics, practitioners, and policymakers seeking a nuanced understanding of the forces shapingmodern organizational success.